Benefits of Establishing Village Owned Enterprises in Diyoudimi Village, Mapia District, Dogiyai Regency, Papua "Based on Law Number 6 of 2014 concerning Villages". - Petrus Tekege (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this paper is to explain that the village of Diyoudimi has abundant natural potential and the incoming village funds are also quite low. In order to find answers on how to manage it, two research methods were used, namely qualitative research methods and quantitative methods. The results show that the regional potential and incoming funds have not been managed and regulated properly so that sometimes it causes chaos, injustice and ambiguity so that people have hopes that it needs to be regulated properly. So that in the future the natural and financial potential of the village can be properly regulated, institutions such as the establishment of Village-Owned Enterprises are needed in accordance with the mandate of Law Number 6 of 2014 concerning Villages.